Long-term effects of 12-month integrated weight-loss programme for children with excess body weight- who benefits most? - Szczyrska, Joanna; Brzeziński, Michał; Szlagatys-Sidorkiewicz, Agnieszka (Frontiers in Endocrinology, 2023)
The aim of the study was to assess long-term effects of the 12-month integrated weight-loss programme in children with excess body weight. We also attempted to identify the determinants of intervention effectiveness. Two groups were included in the analysis: 241 children with excess body weight who participated in the full 12-month intervention (full participation group) and 891 children with excess body weight who did not participate in the intervention (no participation group). Changes in BMI SDS, SBP SDS, DBP SDS and post-exercise HR with a follow-up period of 4 years between this groups were compared. In the full participation group, the reduction in mean BMI SDS was greater, we also observed significantly higher decrease in DBP SDS. Subgroup analysis by age category and sex showed a significant difference in the change in mean BMI SDS (from baseline to follow-up) in the subgroup of younger children and in the subgroup of younger girls. In the subgroup of younger girls significantly higher decrease in DBP SDS and SBP was also observed. Younger children, who participated in the intervention at age 6, particularly girls, benefited the most.